Investigating Multilingual Education in Early Childhood Education in Central Lombok, West Nusa Tenggara, Indonesia - Zobi Mazhabi; Muhammad Yunus; Nur Hasan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study investigates how early childhood educators in Central Lombok, West Nusa Tenggara, perceive and implement multilingual education in their daily classroom practices. Employing a descriptive qualitative design within an interpretivist paradigm, the research seeks to understand how multilingual education is conceptualized, enacted, and shaped by the sociocultural dynamics of early childhood settings. Data were generated through classroom observations, interviews with six teachers and twelve parents, and document analysis, and were analyzed using Braun and Clarke’s six-phase thematic analysis framework. The findings reveal that multilingual education is understood not merely as an instructional method but as a culturally situated, emotionally responsive, and pedagogically strategic practice. Educators perceive multilingualism, particularly the integration of Sasak and Indonesian, as vital for fostering children’s emotional security, enhancing comprehension, and sustaining cultural heritage. In practice, multilingual education is enacted through mixed-medium instruction, fluid translanguaging, the integration of local oral genres, and play-based bilingual activities. These strategies collectively create a rich linguistic ecology that affirms children’s identities while supporting cognitive and socio-emotional development. Future research should extend this inquiry by examining children’s perspectives, exploring longitudinal impacts of multilingual exposure, and analysing institutional and policy factors that shape multilingual practices across diverse early childhood settings in Indonesia.